EVALUASI KARAKTERISTIK BEBERAPA VARIETAS KEDELAI (Glycine max L.Merill) HASIL MUTASI KOLKISIN M2 PADA KONDISI NAUNGAN - Fitra Ramadhani Fitra Ramadhani; Lollie Agustina P.Putri; Hasmawi Hasyim (Jurnal Agroekoteknologi, 2013)
Many potential field is able to be cultivated, which is under the canopy of the plantationand one of the breeding program that can be used obtaining cultivars or varieties are mostlydone by the tecknical breeding mutation. F that,an experiment had been conducted in or hefield of research USU, Medan (+ 25 m asl.) In February-June 2012th by using non-factorialrandomized block design. The results of experimental study that the action plan in severalvarieties had significant effect on flower age, harvesting time, 100 seed weight, theproduction per sample and the production per plot. Value estimate of heritability range from0.12-1. The coefficient of genotypes variations are about 4.64-38.5 and coefficient ofphenotypic variation are about 6.93-38.89. No significant correlation values for allparameters.